Study of pattern and outcome of acute poisoning cases at tertiary care hospital in North India - Naman Aggarwal; Kamal K. Sawlani; Shyam C. Chaudhary; Kauser Usman; Himanshu Dandu; Virendra Atam; Shivani Rani; Rajat Chaudhary (Journal of Family Medicine and Primary Care, 2023)
Introduction: The WHO 2021 data estimate that 2 million lives and 53 million disability-adjusted life-years were lost in 2019 due to exposures to selected chemicals. It is important to know the pattern and outcome of acute poisoning cases for proper planning, prevention and management. Knowing the pattern will also help in designing training modules for primary care physicians to make them aware about newer poisons and their management. Awareness regarding newer poisons consumed is necessary for early identification, initial management and timely referral to higher centres by primary care physicians. This study was performed to see the pattern and outcome of acute poisoning cases in North Indian population and various factors related to outcome. Materials and Methods: This study was conducted in department of medicine of a teaching institute in North India after approval by the Institutional Review Board. Patients admitted in the department during the study and fulfilling the inclusion criteria were enrolled in the study after obtaining consent. Results: A total of 417 patients with poisoning were recruited in the study. Out of 417 patients, majority were males (59.5%). Maximum number of patients were in the age group of 21–30 years (33.8%), and rural population (79.9%) was found to be more affected. Most of the patients were students and private employees. Most common types of poisoning were snakebite (n = 109, 26.1%), organophosphate (n = 49, 11.8%) and aluminium phosphide (n = 39, 9.3%). Out of 417 patients, 349 (83.69%) improved, while 68 (16.3%) expired. Requirement of ventilatory support was most commonly associated with aluminium phosphide poisoning (30.12%) followed by organophosphate poisoning (24.1%). Conclusion: Poisoning was more common in young males and more prevalent in rural population. Pesticides and snakebite were major causes of poisoning. Among suicidal cases, family conflict (problem/altercation with family members/marital discord) was main reason for the consumption of poison. There is need for creation of poison information centre along with separate toxicological units in tertiary care hospitals.